Fourier coefficients associated with the Riemann zeta-function - Basiuk, Yu.V.; Tarasyuk, S.I. (Carpathian Mathematical Publications, 2016)
We study the Riemann zeta-function ζ(s) by a Fourier series method. The summation of |ζ(s)| with the kernel 1/|s|^6 on the critical line Re s = 12 is the main result of our investigation. Also we obtain a new restatement of the Riemann Hypothesis.